Situation Report: Baltic Area, 27 October 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Additional Information on Estonians at Chernobyl / by Toomas Ilves Soviet Respond to the Western Media / by Toomas Ilves Back to the Family Farm / by Toomas Ilves The Chautauqua Conference in the Estonian Press / by Dzintra Bungs The "Baltic Question" at the Chautauqua Conference / by Dzintra Bungs A Latvian American's Impressions of the Chautauqua Conference / by Dzintra Bungs A Young Writer Seeks Asylum on the USA / by Saulius Girnius New Party Second Secretary / by Saulius Girnius Ferry Services Opened between the USSR and GDR / by Saulius Girnius Lithuanian Press on the Chautauqua Conference / by Saulius Girnius Karate Champion Murdered / by Saulius Girnius